Preparation method and application of formaldehyde-free high-thermal-conductivity wood base material

By using a specific proportion of magnesium oxide and magnesium sulfate inorganic adhesives and high thermal conductivity materials in artificial boards, combined with the hot pressing process, the problems of halogen reflux and poor dimensional stability of inorganic adhesives were solved, and high thermal conductivity and low formaldehyde were prepared. Released wood substrate for high performance veneer.

CN119319600APending Publication Date: 2025-01-17POWER DEKOR IND (JIANGSU) CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411634586.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing inorganic adhesives have problems of halogen reflux and poor dimensional stability when producing artificial boards, which affects the performance of the boards. It is difficult for commonly used high-thermal conductivity materials to take into account both thermal conductivity and environmental protection requirements during use.

Method used

Using inorganic adhesives mixed with magnesium oxide, magnesium sulfate and water in a specific proportion, combined with highly thermally conductive materials such as boron nitride, graphite powder or metal powder, high thermally conductive wood substrates are prepared by stirring, pre-pressing, hot pressing and drying. The material is coated with impregnated paper and glue on the surface for hot pressing to form a high environmentally friendly decorative panel.

Benefits of technology

It has achieved high thermal conductivity and high environmental protection grades of wood substrates, with thermal conductivity coefficient of more than 0.5W/(m·K), low formaldehyde emission, significantly improved dimensional stability and thermal conductivity, and is suitable for decorative panel manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136828320000051
    Figure BDA0005136828320000051
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and relates to a preparation method of a formaldehyde-free high-thermal-conductivity wood base material, which comprises the following steps: stirring and drying wood flour, an inorganic adhesive and a high-thermal-conductivity material serving as raw materials to obtain a mixed material with the water content of 8-10%, paving the mixed material on a continuous paving line with the paving amount of 13.5-15.5 kg per square meter, pre-pressing the mixed material by a multi-layer press, and carrying out pressure-maintaining molding to obtain the formaldehyde-free high-thermal-conductivity wood base material. Drying and shaping after preliminary forming; and finally curing and adjusting the moisture content. The heat conductivity coefficient of the base material produced by the method disclosed by the invention is more than 0.5 W / (m.K), the heat conduction efficiency is more than 14 DEG C, the formaldehyde emission is only 0.005 mg / m < 3 > (climatic box method), and the base material has a more efficient heat transfer mode and a more environment-friendly raw material formula. The invention further discloses application of the prepared base material to a veneer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, relates to artificial boards, and in particular to a preparation method and application of a formaldehyde-free high-thermal-conductivity wooden substrate. Background Art

[0002] With the improvement of environmental awareness, consumers are paying more and more attention to formaldehyde, and the requirements for reducing formaldehyde emission from boards are getting higher and higher. In order to meet market demand, inorganic adhesives have been used to replace organic adhesives, such as triamine adhesive, to produce artificial board substrates, so as to achieve formaldehyde-free artificial board substrates.

[0003] Common inorganic adhesives are mainly magnesium oxychloride and silicate. Although they reduce the formaldehyde emission of the board and improve the environmental protection level of the board, other properties of the board are reduced. For example, magnesium oxychloride inorganic adhesives contain halogen elements, which will cause halogen back during use, affecting the performance of the board. The so-called halogen back phenomenon refers to the fact that when the air humidity is high, the surface of the product made with magnesium oxychloride inorganic adhesives absorbs moisture in the air and produces surface moisture, which is then covered with water droplets, and even the water droplets are connected into one piece to form a flow phenomenon; while silicate inorganic adhesives have strong water absorption properties, and the dimensional stability of the boards made is poor.

[0004] The present invention develops a wood substrate with a high environmental protection level and excellent thermal conductivity by using an inorganic adhesive and adding a high thermal conductivity material to the substrate raw material. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to disclose a method for preparing a formaldehyde-free high thermal conductivity wood substrate.

[0006] Technical Solution

[0007] A method for preparing a formaldehyde-free high-thermal-conductivity wooden substrate comprises the following steps: using wood powder, an inorganic adhesive and a high-thermal-conductivity material as raw materials, stirring and drying the mixed material to obtain a moisture content of 8-10%, paving the material on a continuous paving line, and paving the material in an amount of 13.5-15.5 kg per square meter; pre-pressing the material on a multi-layer press, pressure-maintaining molding, drying and shaping the material after preliminary molding, and finally curing the material to adjust the moisture content; wherein the weight ratio of the wood powder, the inorganic adhesive and the high-thermal-conductivity material is 10-12:18-22:0.5-1.5; the inorganic adhesive is a mixture of magnesium oxide, magnesium sulfate and water in weight ratios of 45-58:5-12:36-45; and the high-thermal-conductivity material is any one of boron nitride, graphite powder or metal powder.

[0008] In a preferred disclosed embodiment of the present invention, the wood powder is a uniform wood powder with a particle size of 80 to 400 meshes, and the material is pine, poplar, fir, etc., preferably poplar.

[0009] In a preferred disclosed embodiment of the present invention, the particle size of the high thermal conductivity material is within 30 meshes.

[0010] According to a preferred embodiment of the present invention, the metal powder is aluminum powder or copper powder, preferably aluminum powder.

[0011] According to a preferred disclosed example of the present invention, the mass ratio of the wood powder, the inorganic adhesive and the high thermal conductivity material is 11:20:1.

[0012] In a preferred disclosed example of the present invention, the inorganic adhesive is a mixture of magnesium oxide, magnesium sulfate and water in a mass ratio of 50:8:40.

[0013] According to a preferred embodiment of the present invention, during pre-pressing by the multi-layer press, the pre-pressing pressure is 13.5-15.5 MPa, and the pressure-maintaining molding time is not less than 24 hours.

[0014] In a preferred disclosed embodiment of the present invention, the drying and shaping is performed by hot pressing drying, the hot pressing temperature is 105-120° C., the time is 50-60 minutes, and the moisture content is adjusted to 5-8%.

[0015] The formaldehyde-free high thermal conductivity wooden substrate prepared by the method of the present invention has a density of ≥1.4g / cm 3 , dimensional stability <0.4mm, water absorption thickness expansion rate <1.5%, thermal conductivity ≥14℃ / h, thermal conductivity coefficient ≥0.5W / (m·K).

[0016] The second object of the present invention is to disclose the application of the prepared formaldehyde-free high thermal conductivity wood substrate in the manufacture of decorative panels.

[0017] A finishing method for a formaldehyde-free high thermal conductivity wooden substrate comprises: applying glue to surface impregnated paper and impregnated balancing paper, laying the surface impregnated paper, the formaldehyde-free high thermal conductivity wooden substrate and the impregnated balancing paper in order from top to bottom, hot pressing at a pressure of 4 to 4.5 MPa, a temperature of 170 to 180°C, and a time of 60 to 70 seconds, and inspecting, grading, packaging and warehousing after cooling.

[0018] Wherein, the gram weight of the surface impregnated paper is 75-81g, and the amount of glue applied is 165-220g.

[0019] The impregnated balancing paper has a gram weight of 50 to 80 g and a glue coating amount of 45 to 88 g.

[0020] Beneficial Effects

[0021] The thermal conductivity of the substrate produced by the present invention is above 0.5W / (m·K), the thermal conductivity is above 14°C, and the formaldehyde release is only 0.005mg / m 3 (climate chamber method), which has a more efficient heat transfer method and a more environmentally friendly raw material formula. DETAILED DESCRIPTION

[0022] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0023] Example 1

[0024] A method for preparing a formaldehyde-free high-thermal conductivity wood substrate, comprising 10 parts of poplar wood powder, 18 parts of inorganic adhesive, and 1 part of boron nitride, and then the boards are evenly mixed and paved, with 13.5 kg per square meter. After paving, the board enters the mold and is pre-pressed at room temperature with a pre-pressing pressure of 15.5 MPa. After pre-pressing, the mold is locked and cooled, and the cooling molding time is 24 hours. After molding, the board is demolded and placed in a multi-layer hot press for hot pressing and drying. The hot pressing temperature is 110°C and the time is 50 minutes. No pressure is applied during the hot pressing process. After trimming the substrate, it is placed in a constant temperature and humidity room for curing and preservation. After curing for 7 days, the board is sanded and put into storage. The mass proportions of the components of the inorganic adhesive are as follows: 45 parts of magnesium oxide, 8 parts of magnesium sulfate, and 47 parts of water.

[0025] A finishing method for a formaldehyde-free high thermal conductivity wooden substrate comprises: laying a surface impregnated paper, a formaldehyde-free high thermal conductivity wooden substrate and an impregnated balancing paper in order from top to bottom, hot pressing at a pressure of 4 MPa, a temperature of 170°C and a time of 60 seconds, inspecting, grading and packaging for storage after cooling, wherein the weight of the surface impregnated paper is 75 g and the amount of glue is 165 g; the weight of the impregnated balancing paper is 50 g and the amount of glue is 88 g.

[0026] The prepared decorative panel is recorded as Example 1.

[0027] Example 2

[0028] A method for preparing a formaldehyde-free high-thermal conductivity wood substrate, comprising 12 parts of poplar wood powder, 22 parts of inorganic adhesive, and 1 part of boron nitride, and then the boards are evenly mixed and paved, with 15.5 kg per square meter. After paving, the board enters the mold and is pre-pressed at room temperature with a pre-pressing pressure of 14 MPa. After pre-pressing, the mold is locked and cooled, and the cooling molding time is 24 hours. After molding, the board is demolded and placed in a multi-layer hot press for hot pressing and drying. The hot pressing temperature is 120°C and the time is 50 minutes. No pressure is applied during the hot pressing process. After trimming the substrate, it is placed in a constant temperature and humidity room for curing and storage. After curing for 7 days, the board is sanded and placed in a tray for storage. The mass proportions of the components of the inorganic adhesive are as follows: 50 parts of magnesium oxide, 6 parts of magnesium sulfate, and 44 parts of water.

[0029] A finishing method for a formaldehyde-free high-thermal conductivity wooden substrate comprises: laying a surface impregnated paper, a formaldehyde-free high-thermal conductivity wooden substrate and an impregnated balancing paper in order from top to bottom, hot pressing at a pressure of 4.5 MPa, a temperature of 175°C, and a time of 70 seconds, and inspecting, grading, packaging, and storing after cooling; wherein the weight of the surface impregnated paper is 81 g, and the amount of glue applied is 200 g; wherein the weight of the impregnated balancing paper is 80 g, and the amount of glue applied is 88 g.

[0030] The prepared decorative panel is recorded as Example 2.

[0031] Example 3

[0032] A method for preparing a formaldehyde-free high-thermal conductivity wood substrate, comprising 10 parts of fir powder, 20 parts of inorganic adhesive, and 1 part of graphite, and then the mixture is evenly mixed and then the board is paved, with 14 kg per square meter. After paving, the board enters the mold and is pre-pressed at room temperature with a pre-pressing pressure of 13.5 MPa. After pre-pressing, the mold is locked and cooled, and the cooling molding time is 25 hours. After molding, the board is demolded and placed in a multi-layer hot press for hot pressing and drying. The hot pressing temperature is 105°C, the time is 55 minutes, and no pressure is applied during the hot pressing process. After trimming the substrate, the substrate is placed in a constant temperature and humidity room for curing and storage. After curing for 7 days, the substrate is sanded and placed in a tray for storage. The mass proportions of the components of the inorganic adhesive are as follows: 52 parts of magnesium oxide, 12 parts of magnesium sulfate, and 36 parts of water.

[0033] The surface impregnated paper, formaldehyde-free high thermal conductivity wooden substrate and impregnated balance paper are laid in order from top to bottom and hot pressed at a pressure of 4.5MPa, a temperature of 180°C and a time of 60s. After cooling, they are inspected, graded, packaged and put into storage; the weight of the surface impregnated paper is 81g, and the amount of glue is 200g; the weight of the impregnated balance paper is 60g, and the amount of glue is 76g.

[0034] The prepared decorative panel is recorded as Example 3.

[0035] Example 4

[0036] A method for preparing a formaldehyde-free high thermal conductivity wood substrate, comprising 11 parts of pinewood powder, 18 parts of inorganic adhesive, and 1 part of graphite, and then the boards are evenly mixed and paved, with 14 kg per square meter. After paving, the board enters the mold and is pre-pressed at room temperature with a pre-pressing pressure of 14 MPa. After pre-pressing, the mold is locked and cooled, and the cooling molding time is 25 hours. After molding, the board is demolded and placed in a multi-layer hot press for hot pressing and drying. The hot pressing temperature is 110°C and the time is 55 minutes. No pressure is applied during the hot pressing process. After trimming the substrate, it is placed in a constant temperature and humidity room for curing and storage. After curing for 7 days, the board is sanded and put into storage. The mass proportions of the components of the inorganic adhesive are as follows: 48 parts of magnesium oxide, 10 parts of magnesium sulfate, and 52 parts of water.

[0037] The surface impregnated paper, formaldehyde-free high thermal conductivity wooden substrate and impregnated balance paper are laid in order from top to bottom and hot pressed at a pressure of 4 MPa, a temperature of 180°C and a time of 65 seconds. After cooling, they are inspected, graded, packaged and put into storage; the weight of the surface impregnated paper is 81g, and the amount of glue is 180g; the weight of the impregnated balance paper is 80g, and the amount of glue is 80g.

[0038] The prepared decorative panel is recorded as Example 4.

[0039] The physical and chemical properties of the decorative panels prepared in the above embodiments 1-4 are shown in the following table.

[0040] Veneer panel test results table

[0041]

[0042] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a formaldehyde-free high thermal conductivity wood substrate, using wood powder, inorganic adhesive, and high thermal conductivity material as raw materials, stirring and drying the mixed material to a moisture content of 8-10%, paving on a continuous paving line, with a paving amount of 13.5-15.5 kg per square meter, pre-pressing with a multi-layer press, pressure-maintaining molding, drying and finalizing after preliminary molding, and finally curing to adjust the moisture content, characterized in that: The mass ratio of wood powder, inorganic adhesive and high thermal conductivity material is 10-12:18-22:0.5-1.5, preferably 11:20:1; the inorganic adhesive is a mixture of magnesium oxide, magnesium sulfate and water in a mass ratio of 45-58:5-12:36-45, preferably 50:8:40; the high thermal conductivity material is any one of boron nitride, graphite powder or metal powder.

2. The method for preparing the formaldehyde-free high thermal conductivity wooden substrate according to claim 1, characterized in that: The wood powder is uniform wood powder with a particle size of 80 to 400 meshes, and is made of pine, poplar or fir, preferably poplar.

3. The method for preparing the formaldehyde-free high thermal conductivity wooden substrate according to claim 1, characterized in that: The particle size of the high thermal conductivity material is within 30 meshes.

4. The method for preparing the aldehyde high thermal conductivity wood substrate according to claim 1, characterized in that: The metal powder is aluminum powder or copper powder, preferably aluminum powder.

5. The method for preparing the formaldehyde-free high thermal conductivity wooden substrate according to claim 1, characterized in that: During pre-pressing by the multi-layer press, the pre-pressing pressure is 13.5-15.5 MPa, and the pressure-maintaining molding time is not less than 24 hours.

6. The method for preparing the formaldehyde-free high thermal conductivity wooden substrate according to claim 1, characterized in that: The drying and shaping is performed by hot pressing drying, the hot pressing temperature is 105-120° C., the time is 50-60 minutes, and the moisture content is adjusted to 5-8%.

7. The formaldehyde-free high thermal conductivity wooden substrate prepared according to any one of claims 1 to 6, characterized in that: The substrate density is ≥1.4 g / cm 3 , dimensional stability <0.4mm, water absorption thickness expansion rate <1.5%, thermal conductivity ≥14℃ / h, thermal conductivity coefficient ≥0.5W / (m·K).

8. A finishing method for a formaldehyde-free high thermal conductivity wood substrate as claimed in claim 7, characterized in that: include: Apply glue to the surface impregnated paper and the impregnated balancing paper, lay the surface impregnated paper, formaldehyde-free high thermal conductivity wooden substrate and impregnated balancing paper in order from top to bottom, and hot press at a pressure of 4-4.5MPa, a temperature of 170-180℃, and a time of 60-70s. After cooling, inspect, grade, package and put into storage.

9. The method for finishing a formaldehyde-free high thermal conductivity wooden substrate according to claim 8, characterized in that: The surface impregnated paper has a gram weight of 75 to 81 g and a glue coating amount of 165 to 220 g.

10. The method for finishing a formaldehyde-free high thermal conductivity wooden substrate according to claim 8, characterized in that: The impregnated balancing paper has a gram weight of 50 to 80 g, and a glue coating amount of 45 to 88 g.

Citation Information

Patent Citations

  • Heat-conducting plastic and wood composite material and heating flooring manufactured by using same

    CN102161830A

  • Plastic-wood composite material capable of shielding electromagnetism

    CN103205059A

  • Multifunctional PVC building wood plastic material and preparation method thereof

    CN106700325A

  • Preparation method of high-performance magnesium-series inorganic flame-retardant shaving board

    CN114012857A

  • Flame-retardant heat-conducting wood floor with flame-retardant heat-conducting enhancement layer

    CN114658191A